Đa dạng hóa sinh kế và nâng cao thu nhập người nông dân ở Việt Nam: Bằng chứng thực nghiệm - Nguyễn Hoàng, Long; Ngô Minh , Vũ; Nguyễn Quốc , Bình (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines how livelihood diversification shapes household income in rural Bình Minh town, Vietnam, using panel data from 182 households (HH) from 2020 to 2024 (871 observations). By applying various statistical methods to address endogeneity issues, the results indicate that diversification significantly increases both agricultural and non-agricultural income. Furthermore, the study shows that access to credit amplifies the positive impact of diversification only on non-agricultural income, while diversification mitigates the negative impact of losses due to natural disasters solely on agricultural income. These findings highlight the dual role of diversification as a recovery and accumulation strategy, shaped by income levels, access to credit, and environmental risk levels. Based on these results, the study presents several policy implications aimed at low-income and climate-vulnerable households, expanding access to finance and integrating diversification into rural development and climate adaptation strategies.